Football offside tracking - Mitu, Ishrat Jahan; Chowdhury, Mohammad Hafiz-Ul-Islam; Rahman, Alif; Bhuiyan, Sabbir Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.